Comparison of Tendon Lengthening With Traditional Versus Accelerated Rehabilitation After Achilles Tendon Repair: A Prospective Randomized Controlled Trial. Issue 7 (June 2020) - Okoroha, Kelechi R.; Ussef, Najib; Jildeh, Toufic R.; Khalil, Lafi S.; Hasan, Laith; Bench, Carter; Zeni, Ferras; Eller, Erik; Moutzouros, Vasilios
Background: Early weightbearing protocols after Achilles tendon repair promote mobilization, yet little is known about their effect on tendon lengthening. Purpose: To evaluate tendon lengthening after Achilles tendon repair with accelerated rehabilitation. Study Design: Randomized controlled trial; Level of evidence, 1. Methods: Patients undergoing primary repair for acute Achilles tendon ruptures consented to have tantalum beads placed within the tendon. Patients were randomized into either a traditional (weightbearing at 6 weeks) or accelerated (graduated weightbearing at 2 weeks) rehabilitation group. The primary outcome of the study was postoperative tendon elongation as measured by radiostereometric beads. Secondary outcomes included Achilles Tendon Total Rupture Score (ATRS) and Patient-Reported Outcomes Measurement Information System Pain Interference Short Form (PROMIS PI-SF) score. Results: All 18 patients included in the final analysis were found to have significant tendon lengthening after surgery, with a mean lengthening of 15.9 mm. No significant differences were found in overall lengthening between the traditional and accelerated rehabilitation groups (15.3 ± 4.5 vs 16.4 ± 4.7 mm, respectively; P = .33) at final follow-up. The repair site in each group was found to lengthen more than the intratendinous site (traditional group, 13.2 vs 2.1 mm; accelerated group, 16.8 vs −0.4 mm); however, no difference in lengthening was seen between groups ( P = .82 and P = .31, respectively). The greatest amount of lengthening occurred between 2 and 6 weeks, and the least amount of lengthening occurred between 6 and 12 weeks, with no difference between the traditional and accelerated groups at these time points ( P = .84 and P = .38, respectively). No differences were noted in ankle range of motion (dorsiflexion, P = .16; plantarflexion, P = .08) or outcome scores (ATRS, P = .56; PROMIS PI-SF, P = .54). Conclusion: This study's findings demonstrate that all patients undergoing operative repair of Achilles tendon ruptures had lengthening after surgery. No difference was found in tendon lengthening (repair site or intratendinous) at any time point between patients undergoing traditional versus accelerated rehabilitation postoperatively. The greatest amount of lengthening was found to occur between 2 and 6 weeks postoperatively, and tendon lengthening decreased significantly after 6 weeks. Registration: NCT04050748 (ClinicalTrials.gov identifier).